(untitled) (Nexus International Journal of Science and Education, 2024)
The study determined the extent of instructional leadership skills and the extent of performance of public elementary school master teachers. This study employed a non-experimental quantitative research design utilizing descriptive-correlation method. Validated questionnaire and Universal sampling procedure were utilized considering the minimal number of teachers in the research locale. Two hundred fifty (250) public elementary school teachers were the respondents of the study. Using mean, pearson-r, and regression analysis, the findings revealed that the instructional leadership skills were extensive while the extent of performance of public elementary school master teachers was also extensive. Moreover, the overall results disclosed that indicators for the instructional leadership skills were positively correlated to the performance of public elementary school master teachers. Further, results from the regression analysis revealed the following have a strong influence of instructional leadership skills on the performance of public elementary school master teachers: instruction, research, mentoring and coaching, and observation and supervision. It was recommended that the master teachers evaluate and redesign the use of time and school schedules to increase opportunities for professional learning and collaboration, including participation in professional learning communities, peer coaching and observations across classrooms, and collaborative planning. It was also recommended that master teachers regularly conduct needs assessments to identify areas of professional learning most needed and desired by educators.